2015
DOI: 10.31899/rh9.1057
|View full text |Cite
|
Sign up to set email alerts
|

Standard Days Method of contraception: Evidence on use, implementation, and scale up

Abstract: Since the early 2000s, the Standard Days Method (SDM) of family planning has been tested, introduced, and scaled up in countries around the world. SDM is a fertility awareness-based method for avoiding unprotected intercourse during the fertile period, days eight through 19 of a woman's menstrual cycle (for women whose cycles range from 26 to 32 days). Most SDM users utilize a visual aid-CycleBeads ®-to assist their correct use of SDM. In a 2002 trial, the method's first year failure rate (5 per 100 woman year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
(149 reference statements)
1
7
0
Order By: Relevance
“…When used correctly, the failure rate is only 5 per 100 woman years (Arevalo et al, 2002). Positive attributes of SDM, according to women, are that it does not have health risks or side effects, it is effective, simple to use, affordable, does not involve medication, and involves partners in family planning (Bekele and Fantahun 2012;IRH 2013b;Kursun et al, 2014, Blair et al 2007, Capo-Chichi and Anastasi 2005Wright et al, 2015).…”
Section: Standard Days Methodsmentioning
confidence: 99%
“…When used correctly, the failure rate is only 5 per 100 woman years (Arevalo et al, 2002). Positive attributes of SDM, according to women, are that it does not have health risks or side effects, it is effective, simple to use, affordable, does not involve medication, and involves partners in family planning (Bekele and Fantahun 2012;IRH 2013b;Kursun et al, 2014, Blair et al 2007, Capo-Chichi and Anastasi 2005Wright et al, 2015).…”
Section: Standard Days Methodsmentioning
confidence: 99%
“…1 The SDM has been researched, developed, promoted and marketed through the Institute of Reproductive Health (IRH) at Georgetown University, USA, and Cycle Technologies, a for-profit company, which sells CycleBeads® and CycleBeads® Online (web-based application), and produces iCycleBeads® and DOT™ ("Dynamic Optimal Timing") (mobile phone applications) [7][8][9]. SDM introduction, scale up, and other activities have involved a wide range of international organisations, 2 largely funded by the United States Agency for International Development (USAID) [10,11]. The Bill and Melinda Gates Foundation has also provided support for pilot efforts in two countries [10].…”
Section: Introductionmentioning
confidence: 99%
“…SDM introduction, scale up, and other activities have involved a wide range of international organisations, 2 largely funded by the United States Agency for International Development (USAID) [10,11]. The Bill and Melinda Gates Foundation has also provided support for pilot efforts in two countries [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding family planning options has been shown to increase contraceptive use, as a wider choice of methods improves the ability to meet women's and couples' needs (Ross and Stover 2013). SDM has been introduced and assessed in different facility and communitybased service delivery settings for over 15 years (Gribble et al 2008;Wright, Iqteit, and Hardee 2015). A number of studies have demonstrated an overall increase in contraceptive prevalence rates where SDM has been made available, including in Rwanda Blair et al 2007;Gribble et al 2008;Arévalo et al 2010).…”
mentioning
confidence: 99%